Interstitial carbon induced FCC-Ti exhibiting ultrahigh strength in a Ti37Nb28Mo28-C7 complex concentrated alloy. (15th January 2021) - Jiang, Shan; Huang, Lujun; Gao, Xiang; Liu, Gang; Zhang, Rui; Jiao, Yang; Peng, Shang; An, Qi; Wang, Shuai; Geng, Lin
Abstract: An interstitial carbon induced-FCC-Ti was observed in a carbon-doped Ti37 Nb28 Mo28 -C7 (atomic percentage) complex concentrated alloys (TNMC alloys). Not only the true crystal structure of this FCC-Ti was directly characterized using Cs-corrected STEM, but also the mechanical properties were tested by nanoindentation and micro-pillar compression for the first time. The FCC-Ti exhibited a high nano hardness of 17.8 GPa and a high elastic modulus of 233.1 GPa. The micropillar compression tests demonstrated the ultrahigh strengths of the interstitial C induced FCC-Ti (4.48 GPa at [1 1 1] direction, 2.67 GPa at [1 0 1] direction, and a CRSS of 1.12 ± 0.07 GPa). The nature of this FCC allotropic transformation was determined to be a rearrangement of lattice structure caused by interstitial C atoms, based on ab-initio studies. Findings in this study provide insights into the characteristics of FCC-Ti as well as the role of interstitial atoms in RCCAs which could open up unlimited possibilities in future material designing. Graphical abstract: Image, graphical abstract